2021
DOI: 10.30722/ijisme.29.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Videos, Conceptual Understanding and Self-Efficacy in the Time of COVID

Abstract: Advances in technology offer new opportunities for teaching. Many students engage with online videos that enable them to watch, and re-watch these support materials flexibly and at their own pace. In our large-enrolment introductory first-year physics unit, many students find the content very challenging. To support their learning, we have developed short videos of 4-7 minutes explaining concepts and providing demonstrations of the problem-solving process. Our study was originally designed to evaluate and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The image principle suggests that seeing the instructor on screen does not necessarily improve learning, and the variability in student perceptions around the benefit of instructor visibility (Table 5) is in accordance with published literature (Kizilcec et al, 2014;Korving et al, 2016;Wang & Antonenko, 2017). "Lightboard videos" have been suggested as a single presentation style that encompasses instructor visibility and hand-drawing diagrams on screen (Jose, Kochandra, & Daniel, 2021), but the present study found no student consensus around the optimal amount of on-screen instructor visibility. Filming the instructors alongside slideshow screen recordings, however, opens possibilities for the creation of new presentation styles through simple video editing techniques (e.g., "picture-in-picture" with the instructor's face in the corner of the slide).…”
Section: Discussionsupporting
confidence: 80%
“…The image principle suggests that seeing the instructor on screen does not necessarily improve learning, and the variability in student perceptions around the benefit of instructor visibility (Table 5) is in accordance with published literature (Kizilcec et al, 2014;Korving et al, 2016;Wang & Antonenko, 2017). "Lightboard videos" have been suggested as a single presentation style that encompasses instructor visibility and hand-drawing diagrams on screen (Jose, Kochandra, & Daniel, 2021), but the present study found no student consensus around the optimal amount of on-screen instructor visibility. Filming the instructors alongside slideshow screen recordings, however, opens possibilities for the creation of new presentation styles through simple video editing techniques (e.g., "picture-in-picture" with the instructor's face in the corner of the slide).…”
Section: Discussionsupporting
confidence: 80%